SISTEM PENGENDALIAN INTENSITAS CAHAYA PADA INKUBATOR BAYI UNTUK PROSES FOTOTERAPI MENGGUNAKAN KONTROL FUZZY - Lumbantoruan, Natalia; Rahmadwati, n/a; Rusli, Moch. (Jurnal Mahasiswa TEUB, 2024)
Phototherapy is one of the processes to overcome jaundice that usually occurs in premature babies, namely by providing blue light. Jaundice or hyperbilirubinemia is one of the problems or disorders in babies who experience premature birth. One of the important things in providing phototherapy is that the intensity of the light given greatly affects the effectiveness of the process.Therefore, it is necessary to control the light intensity to keep it as desired. In this research, the light intensity control system in phototherapy uses a BH1750 sensor as a sensor to detect light intensity and fuzzy logic control is used to keep the light intensity produced in the incubator within the required range, which is 19-24.5 lux. The fuzzy control used is the Sugeno method with 3 stages, namely fuzzification, rule inference, and defuzzification. The result of the system response is the light intensity as required. Testing is done by setting a set point at a light intensity of 22 lux where the settling time is obtained around 8 seconds, there is no overshoot, and has a steady state error below 5%, which is 2.27%. Keywords: Phototherapy, Light Intensity, Fuzzy Control